2017
DOI: 10.21833/ijaas.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and interlaminar shear study of hybrid woven kenaf/recycled GFRP (rGFRP) composites subjected to bending load

Abstract: Delamination known as the failure at the interface between different layers is one of critical failure mechanism for laminates composites. Hybrid laminate composites comprised of unique ply material and structure, unwanted interlaminar shear stresses may occur between ply laminate due to different material behavior and properties. The aim of this research is to study structural integrity effect of interleaf glass mat and recycled GFRP waste (rGFRP) in woven kenaf reinforcement polyester composite. The properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Polyester composites with fibre volume fraction were kept constant. Results showed that the flexural strength improved by up to 47.5% and indicated that the recycled GFRP could replace glass fibre as reinforcement [ 92 ]. Abd El-baky and Attia investigated the tensile and bending performances of hybrid jute-glass-carbon epoxy composites with different layer configurations.…”
Section: Mechanical Properties Of Interply Hybrid Compositesmentioning
confidence: 99%
“…Polyester composites with fibre volume fraction were kept constant. Results showed that the flexural strength improved by up to 47.5% and indicated that the recycled GFRP could replace glass fibre as reinforcement [ 92 ]. Abd El-baky and Attia investigated the tensile and bending performances of hybrid jute-glass-carbon epoxy composites with different layer configurations.…”
Section: Mechanical Properties Of Interply Hybrid Compositesmentioning
confidence: 99%
“…The interlaminar shear strengths (ILSS) effectively provide information about the adhesion between the fiber and the matrix [43,44]. The ILSS was calculated using the equation [44,45,46]; (3) where P max is the maximum applied load on the specimen, b and t are the width and thickness of the specimen respectively.…”
Section: Interlaminar Shear Strengthmentioning
confidence: 99%